Foreword - Vol 1 - Benson, Ciarán (Irish Journal of Arts Management and Cultural Policy, 2013)
Professor Emeritus of Psychology, University College Dublin, Ciarán Benson, outlines the important contribution a research-focused journal on arts management and cultural policy could present the island of Ireland. Sometimes it is only when something arrives that you realise that it was missing and has been missed. The Irish Journal of Arts Management and Cultural Policy is just such an arrival. While there has long been a commitment to actively shape cultural policy in and for Ireland, often as a means of furthering nationalism, it is only in the last forty years or so that a more self-critical and diverse constituency has emerged with a common commitment to making ‘culture’, in all its rich variety, a central part of Irish social life and political discourse.